Perilaku Penggunaan Smartphone pada Pekebun Kelapa Sawit dalam Peremajaan Kelapa Sawit pada Gapoktan Manunggal Sakti Desa Sialang Sakti Kabupaten SIak - Andriani, Yulia; Yulida, Roza; Rosnita; Tunisa, Fadilah (Jurnal Studi Komunikasi dan Media, 2024)
The implementation of the oil palm replanting program for smallholders (PSR) has experienced many problems, especially related to the flow of information and communication between various parties and smallholders. The purpose of this study is to determine the behavior of farmers in the use of smartphones that adopt TAM theory.  This research was conducted in Sialang Sakti Village, Siak Regency. The number of respondents in the study amounted to 30 people who were taken purposively with consideration of farmers who had participated in PSR program. Data analysis using descriptive analysis. The result of this study is that perceptions of expediency of use and attitudes towards use fall into the very high category. The perception of ease of use and behavioral interest falls into the high category. Real conditions of use fall into the category of moderate. It is necessary to develop social media based applications to implement replanting and training in the use of Information and Communication Technology (ICT) for farmers so that smartphone ownership can attract interest in actual behavior and use of ICT in oil palm replanting.